2013
DOI: 10.1155/2013/382350
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Metabolism Characteristics of Rutin in Caco‐2 Cells

Abstract: The intestinal absorption and metabolism characteristics of the potentially beneficial polyphenol rutin were studied by measuring the intracellular accumulation and transport of rutin into Caco-2 cells with the sensitive and reliable analytical method of HPLC-coupled tandem mass spectrometry. Rutin and glucuronidated rutin were absorbed differently by the basolateral and apical membranes, and rutin showed differential permeability through the apical and basolateral sides. Approximately 33% of the rutin was met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…As shown in Figure , rutin, pure and from BF, was susceptible to being transported outside of the cells, but when HEE was tested, the efflux of the marker was practically reversed. According to our results and previous reports, P‐gp will be involved in this efflux. Hence, the lower ER of rutin from HEE could be a consequence of the saturation of this transporter, that would be favoured by the more complex mixture of compounds present in crude extracts (comparatively to fractions) and by the higher starting concentration of HEE used in the experiments (equivalent to 10 μ m for HEE vs 5 μ m for BF).…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Figure , rutin, pure and from BF, was susceptible to being transported outside of the cells, but when HEE was tested, the efflux of the marker was practically reversed. According to our results and previous reports, P‐gp will be involved in this efflux. Hence, the lower ER of rutin from HEE could be a consequence of the saturation of this transporter, that would be favoured by the more complex mixture of compounds present in crude extracts (comparatively to fractions) and by the higher starting concentration of HEE used in the experiments (equivalent to 10 μ m for HEE vs 5 μ m for BF).…”
Section: Discussionsupporting
confidence: 90%
“…The outcomes revealed that plasma flavonoids were significantly elevated in rutin-supplemented group, fortunately, without any adverse changes in blood chemistry or indices of liver function. Additionally, Zhang et al ., has reported the absorption and metabolism characteristics of rutin in the intestinal-derived Caco-2 cells (33) and the pharmacokinetics of rutin has been studied in rats after oral administration with the identification of its associated metabolites in urine and feces by Ou-yang et al (34). Furthermore, various antitumor studies have been reported for rutin in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…To add, rutin 4 ( Figure 2, Table 3) was isolated from Ruta graveolens grass naphtha 76 . Zhang et al 76 reported that rutin decreased the bioavailability of cyclosporine through activation of P-gp.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Zhang et al 76 reported that rutin decreased the bioavailability of cyclosporine through activation of P-gp. Thus, P-gp is involved in the transmembrane transport and intracellular accumulation of rutin in human colonic cancer cells (Caco-2).…”
Section: Flavonoidsmentioning
confidence: 99%